Review Article: Phytochemical Screening and Potential Biological Activities of Lahuna Plants ( Chromolaena odorata L.) - Jumrah, Elfira (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Chromolaena odorata L., locally known as the Lahuna plant, is a tropical plant with great potential in traditional medicine. This study uses a qualitative approach method that critically examines the results of previous studies on the phytochemical content and potential biological activity of the Chromolaena odorata L. plant. This review article discusses the results of phytochemical screening and the potential biological activity of various secondary metabolite compounds contained in the plant, such as flavonoids, alkaloids, saponins, tannins, and terpenoids. Various studies have shown that C. odorata has broad pharmacological activities, including antibacterial, anti-inflammatory, antioxidant, and wound-healing agents. With its abundant bioactive content, this plant has great potential to be developed as a source of natural medicine. However, its clinical use still requires further scientific validation through toxicity tests, pharmacodynamics, and clinical trials. This article aims to provide a scientific basis for the potential of C. odorata in the field of phytopharmaceuticals and encourage further research for its development.